THE INFLUENCE OF POSTER AND ANIMATED VIDEO MEDIA ON FRUIT AND VEGETABLE CONSUMPTION ON CHILDREN'S KNOWLEDGE AT SDN KARAWANG KULON II - Hartanti, Niken; Kurniasari, Ratih (HEARTY, 2024)
Knowledge and attitude are some of the factors contributing to low consumption of fruits and vegetables in children. Knowledge and attitude also influence children's eating habits. Therefore, the aim of this study is to analyze the influence of a dietary intervention using posters and animated videos on the knowledge of elementary school children. The research plan employs a quasi-experimental design by providing nutrition education interventions to three groups of students in Karawang Regency, West Java in May 2023. There are 30 elementary school students. Questionnaire data were analyzed using the Wilcoxon rank test for abnormal data and paired t-test for normal data to measure the extent of data differences. After the intervention, students' knowledge regarding the animated video media significantly increased (p-value = 0.032), making animated video media one of the effective ways to improve the nutritional knowledge of elementary school students and change attitudes for the better.